A HALAL LABEL FOR MSMES: OBSTACLES AND CHALLENGES FACED HALAL LABEL FOR MSMES: OBSTACLES AND CHALLENGES FACED - Endang Kartini Panggiarti; Abdul Mustaqim; Enriko Teja Sukmana (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
The aim of this study is to further study the role of halal labels on a package of food products processed by MSMEs, and explore further about the obstacles and challenges faced by MSMEs. The majority of Indonesians are Muslims, of course, food choices are a top priority. The number of food choices in this market must certainly be in accordance with Islamic guidance, that is only halal food that can be consumed. To fulfill that, of course, it is the obligation and responsibility of producers/MSMEs. This research method uses a qualitative approach with case study design from 2015 to 2020. The results obtained are still available in some areas both concumers and producers/MSMEs who are less concerned about the inclusion of halal labels in each product. In addition, there is still a high sense of consumer confidence in the production that the food served is halal because they know the natural raw materials used by producers without, they having halal labels. The recommendation of this study is that there still needs to be socialization about the importance of halal certification in every packaged product for both consumers and manufacturers/MSMEs.